Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1063/5.0024437
|View full text |Cite
|
Sign up to set email alerts
|

Low intermittent flow promotes rat mesenchymal stem cell differentiation in logarithmic fluid shear device

Abstract: Bone marrow mesenchymal stem cells are an ideal candidate for bone tissue engineering due to their osteogenic potential. Along with chemical, mechanical signals such as fluid shear stress have been found to influence their differentiation characteristics. But the range of fluid shear experienced in vivo is too wide and difficult to generate in a single device. We have designed a microfluidic device that could generate four orders of shear stresses on adherent cells. This was achieved using a unique hydraulic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Studies using human bone marrow-derived MSC reported that shear stress at 0.4–2.2 Pa increased the expression of BMP-2, bone sialoprotein (BSP), osteopontin (OPN) and ALP together with enhanced calcium deposition within 7 days. 16 18 Further comparable results were reported in MSC isolated from rodents at 1.09 mPa–1.03 Pa. 19 Compared with 2D models, however, there is only limited evidence on fluid flow-induced osteogenesis in the 3D environment. Human fetal osteoblasts, hFOB 1.19, subjected to cyclic fluid shear stress at 3.93 mPa for 28 days on functionalised polycaprolactone/hydroxyapatite scaffolds, exhibited increased ALP activity, extracellular matrix (ECM) formation and mineralisation.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Studies using human bone marrow-derived MSC reported that shear stress at 0.4–2.2 Pa increased the expression of BMP-2, bone sialoprotein (BSP), osteopontin (OPN) and ALP together with enhanced calcium deposition within 7 days. 16 18 Further comparable results were reported in MSC isolated from rodents at 1.09 mPa–1.03 Pa. 19 Compared with 2D models, however, there is only limited evidence on fluid flow-induced osteogenesis in the 3D environment. Human fetal osteoblasts, hFOB 1.19, subjected to cyclic fluid shear stress at 3.93 mPa for 28 days on functionalised polycaprolactone/hydroxyapatite scaffolds, exhibited increased ALP activity, extracellular matrix (ECM) formation and mineralisation.…”
Section: Introductionsupporting
confidence: 59%
“…24,46,47 Hence, the results provide evidence that osteogenesis of BMSC on 3D non-osteoinductive scaffolds can be induced solely by fluid flow in the absence of osteogenic supplements as reported in 2D systems where fluid effect is purely represented as shear stress. 14,15,19,20 Various types of bioreactors have been developed for bone tissue engineering. Each of the systems has distinctive features, and therefore, the identification of experimental parameters is the first step in reconciling the experimental data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Load-induced FFSS could change cell shape. One classic 2D model to explore the effect of load-induced FFSS is parallel-plate flow chamber ( Yourek et al, 2010 ; Dash et al, 2020 ). Using this model, it was confirmed that short-term continuous FFSS (9 dynes/cm 2 ) for 24 h could promote the osteogenic differentiation of MSCs without chemically osteoinductive molecules ( Yourek et al, 2010 ).…”
Section: Distinctive Biophysical Stimuli For Bone Tissue Engineeringmentioning
confidence: 99%